2007
DOI: 10.1111/j.1462-2920.2007.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of intraclonal adaptation mechanisms of Pseudomonas brassicacearum facing cadmium toxicity

Abstract: SummaryPseudomonas brassicacearum forms phenotypic variants in vitro as well as in planta during root colonization under natural conditions, leading to subpopulations (phase I and II cells) that differ in colony morphology and production of exoenzymes/ secondary metabolites. The maximal concentration of cadmium allowing both variants growth was 25 mM; however, phase II cells accumulated fivefold higher Cd than phase I cells, even though both variants showed the same growth rate and kinetics, comprising a long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 55 publications
(66 reference statements)
3
38
0
Order By: Relevance
“…Previous studies have shown that phenotypic switching from phase I to phase II in P. brassicacearum involves downregulated transcription of lipA (lipase), phlACBD (DAPG biosynthesis), and hcnABC (hydrogen cyanide biosynthesis) (12,31). Using lipA, phlD, and hcnB as molecular markers, we confirmed by RT-PCR that the transcriptional expression of these genes was low in the gacS-negative variant V1 by comparison with the wild type (Fig.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Previous studies have shown that phenotypic switching from phase I to phase II in P. brassicacearum involves downregulated transcription of lipA (lipase), phlACBD (DAPG biosynthesis), and hcnABC (hydrogen cyanide biosynthesis) (12,31). Using lipA, phlD, and hcnB as molecular markers, we confirmed by RT-PCR that the transcriptional expression of these genes was low in the gacS-negative variant V1 by comparison with the wild type (Fig.…”
Section: Resultssupporting
confidence: 64%
“…This phenomenon also occurs in the rhizosphere of Arabidopsis thaliana (2). To identify the regulatory components controlling phenotypic switching in strain NFM421, we initiated a transcriptomic analysis using homemade microarrays (31). The most remarkable changes differentiating the variants from the wild type were seen in transcripts related to biofilm formation as type IV pili and secondary metabolism as 2,4-diacetylphloroglucinol (DAPG) (see Table S2 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent of the actual chemical speciation of Cd 2+ and Ni 2+ in the mineral media used for this study, the defined and comparable conditions should thus supply significant information about the interactive influence of Ca 2+ and Mg 2+ at different concentrations as well as of EDTA on growth of P. brassicacearum and on the inhibitory effect caused by Cd 2+ and Ni 2+ . Since the toxic effect of Cd 2+ on P. brassicacearum has been characterised as a bacteriostatic inhibition of growth, but not as a bacteriocidal inactivation (Pages et al 2007), the respective maximum specific growth rate μ max [per hour] of this organism is used as an indicator for the magnitude of toxicity caused by Cd 2+ , Ni 2+ and EDTA.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study with cells of P. brassicacearum strain NFM421, Pagès et al reported a maximum tolerable Cd 2+ concentration of 25 μmol L −1 when using a tenfold diluted TSB/10 medium for the cultivations (Pages et al 2007). In the present study, however, the synthetic mineral 4C medium was used to specifically investigate the influence of Cd 2+ and Ni 2+ on growth of P. brassicacearum (type strain CFBP 11706) under various defined conditions.…”
Section: Influence Of CD 2+ and Ni 2+ On Growth Of P Brassicacearum mentioning
confidence: 97%